ROS-Mediated Necrosis by Glycolipid Biosurfactants on Lung, Breast, and Skin Melanoma Cells - Haque, Farazul; Khan, Mohd Sajjad Ahmad; AlQurashi, Naif (Frontiers in Oncology, 2021)
Cancer is one of the major leading causes of death worldwide. Designing the new anticancer drugs is remained a challenging task due to ensure complexicity of cancer etiology and continuosly emerging drug resistance. Glycolipid biosurfactants are known to possess various biological activities including antimicrobial, anticancer and antiviral properties. In the present study, we sought to decipher the mechanism of action of the glycolipids (lactonic-sophorolipd, acidic-sophorolipid, glucolipid and bolalipid) against cancer cells using lung cancer cell line (A549), breast cancer cell line (MDA-MB 231) and mouse skin melanoma cell line (B16F10). Scratch assay and fluorescence microscopy revealed that glycolipids inhibit tumorous cell migration possibly by inhibiting actin filaments. Flourescence activated cell sorter (FACS) analysis exhibited that lactonic sophorolipid and glucolipid both induced the reactive oxygen species, altered the mitochondrial membrane potential (ΔΨ), and finally led to the cell death by necrosis. Furthermore, combinatorial effect of lactonic-sophorolipd and glucolipid demonstrated synergistic interaction against on A549 cell line whereas additive effect on MDA-MB 231 and B16F10 cell lines. Our study has highlighted that lactonic-sophorolipd and glucolipid could be useful for developing new anticancer drugs either alone or in combination.